Ambroxol inhibits mucoid conversion of Pseudomonas aeruginosa and contributes to the bactericidal activity of ciprofloxacin against mucoid P. aeruginosa biofilms. Issue 7 (22nd April 2016) - Wang, Wenlei; Yu, Jialin; He, Yu; Wang, Zhengli; Li, Fang
Abstract : Pseudomonas aeruginosa is an opportunistic human pathogen that can cause severe infections in immunocompromised individuals. Because it forms biofilms, which protect against host immune attack and increase resistance to conventional antibiotics, mucoid P. aeruginosa is nearly impossible to eradicate. Moreover, mucoid conversion of P. aeruginosa in cystic fibrosis (CF) patients leads to poor outcomes. This conversion is mainly due to mucA gene mutation, which is thought to be induced by polymorphonuclear leukocytes (PMNs) and the reactive oxygen species they release. Ambroxol, a mucolytic agent with antioxidant characteristics, is used clinically, and this compound has recently been demonstrated to possess anti‐biofilm properties. In this study, we found that ambroxol inhibits the H2 O2 ‐mediated conversion of P. aeruginosa from a non‐mucoid to a mucoid phenotype, an effect that is due to its antioxidant property against H2 O2 . Furthermore, the bactericidal activity of ciprofloxacin against mucoid P. aeruginosa biofilms was increased in vitro when used in combination with ambroxol.